Social inequalities in Europe: Facing the challenge - Jutta Allmendinger; Ellen von den Driesch (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2014)
This discussion paper describes the extent of social inequalities both within and between the countries of the European Union. In the first three chapters we address the micro level of individual life courses: education, employment and income. The following chapters analyse the societal consequences of inequalities. Chapter 4 looks at the unequal distribution of financial resources, while chapter 5 addresses the social and political outcomes of financial inequalities. In sum, there is mounting scientific evidence that various forms of educational, employment and financial inequalities increase over time. Moreover, societal exclusion is likely to lead to forms of political exclusion that is, a depoliticisation of socially excluded groups or to various forms of political extremism. This is an alarming sign for the future of European democracies and is in glaring contradiction to the democratic political values of equality enshrined in the Treaties.
Keywords: D31; I24; I26; I30; J21; J31; 300; Europe; Social inequalities; Income; Education; Employment; Returns to Education